Exploring The Effectiveness of Digital Learning Platforms for Improving Financial Skills: The Case of YouTube - Sutirman, Sutirman; Imrona, Wargo; Sholikah, Mar'atus (FKIP Universitas Lampung, 2025)
Exploring The Effectiveness of Digital Learning Platforms for Improving Financial Skills: The Case of YouTube. Objective: YouTube is a digital platform that can be used for formal and informal education. Very little research still reveals the use of YouTube as a learning resource in schools for financial management material. Therefore, this research aims to explore using YouTube as a digital learning resource for improving financial ability. Methods: This research uses qualitative and quantitative methods with descriptive statistics. The subjects in this research were teachers and students. Data collection was carried out through questionnaires and interviews to gain a comprehensive understanding of user perceptions and learning outcomes. Findings: Research found that 84% of respondents agreed to use YouTube as a digital learning resource in learning Financial Management material, and 77% believe they can learn more by watching subject-related videos on YouTube than by reading books. In addition, students' responses strongly agreed with using YouTube as a digital learning resource for learning financial management. YouTube stores material in long-term memory, making it easier for students to review the material, so that student understanding increases. The visual and auditory elements of YouTube videos enhance engagement and retention. YouTube is also effective as a digital learning platform for improving financial skills. Teachers also acknowledged that YouTube helps make abstract financial concepts more concrete through visual explanations. Conclusion: So, YouTube has the potential to become an effective digital platform used for learning, particularly in improving students' financial skills. The accessibility, diversity of content, and user-friendly nature of YouTube make it a valuable supplement to traditional learning resources in the digital age. Future research is recommended to explore the long-term impacts of YouTube-based learning on students' financial behaviour. Keywords: digital learning platform, financial ability, youtube.